A technique to treat Descemet’s membrane detachment following cataract surgery - Liu, Wenjie; Ma, Jack X.; Tan, Xin; Chai, Feiyan; Liu, Jiewei (Frontiers in Medicine, 2024)
We describe a technique to reattach the detached Descemet’s membrane, following cataract surgery. From the main clear corneal cataract incision, aqueous humor is ejected completely by apposition of the cornea to the iris for approximately 3 s. This ensures the fluid in the space between the stroma and Descemet’s membrane is ejected and the detached Descemet’s membrane returns to its original position. Sterile air is injected through a paracentesis 180 degrees away from the Descemet’s membrane detachment, to maintain a complete air-filled chamber. Full air tamponade is maintained for 20 min, following which one-third of the air is ejected from the chamber to prevent an increase of postoperative intraocular pressure.